2020
DOI: 10.1161/atvbaha.119.313636
|View full text |Cite|
|
Sign up to set email alerts
|

Low and Oscillatory Wall Shear Stress Is Not Related to Aortic Dilation in Patients With Bicuspid Aortic Valve

Abstract: Objective: To assess the relationship between regional wall shear stress (WSS) and oscillatory shear index (OSI) and aortic dilation in patients with bicuspid aortic valve (BAV). Approach and Results: Forty-six consecutive patients with BAV (63% with right-left-coronary-cusp fusion, aortic diameter ≤ 45 mm and no severe valvular disease) and 44 healthy volunteers were studied by time-resolved 3-dimensional phase-contrast magnetic resonance imaging. WSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…The results presented herein confirm the findings of Dux-Santoy et al[ 26 ] suggesting that hemodynamics resulting due to BAV are not associated with low and oscillating TAWSS in the AAo (Figs 10 and 14 ); on the contrary, strong and unidirectional, eccentric aortic jets lead to high TAWSS/ low OSI on large parts of the AAo wall. Fig 17 shows that high OSI regions generally matched with those experiencing low TAWSS, but these regions, on average, made up less than 20% of the AAo surface area with BAVs ( Fig 18 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results presented herein confirm the findings of Dux-Santoy et al[ 26 ] suggesting that hemodynamics resulting due to BAV are not associated with low and oscillating TAWSS in the AAo (Figs 10 and 14 ); on the contrary, strong and unidirectional, eccentric aortic jets lead to high TAWSS/ low OSI on large parts of the AAo wall. Fig 17 shows that high OSI regions generally matched with those experiencing low TAWSS, but these regions, on average, made up less than 20% of the AAo surface area with BAVs ( Fig 18 ).…”
Section: Discussionsupporting
confidence: 91%
“…Focused investigations into the association between BAV aortopathy and the underlying blood flow appear to suggest that the hemodynamic determinants of aortic diameter modifications might follow a different mechanism. A recent study by Dux-Santoy et al [ 26 ] compared WSS on the AAo in 46 BAV patients to 44 healthy volunteers using time-resolved 3D MRI and found that regions exposed to low and oscillating wall shear stress in BAV patients did not match those with the highest prevalence of dilation. In other studies, the group also showed, through cardiac MRI analysis and in silico modeling that BAV patients exhibited strong helical flows in the aorta, with increased axial circulation [ 27 ] and circumferential wall shear stress [ 28 ] compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are serious limitations in both spatial and temporal resolution of the signals and data are corrupted by noise-like phase error [17]. Recently, multiple studies have used 4D flow MRI for the assessment of haemodynamics of the aorta evaluating aortic flow patterns, WSS and regional aortic stiffness (via pulse wave velocity (PWV) in the thoracic aorta of bicuspid aortic valve [8,[18][19][20] and MFS [21,22] patients). Outlet boundary conditions can be simulated using the Windkessel model.…”
Section: Introductionmentioning
confidence: 99%
“…Wall shear stress has also been extensively studied in patients with BAV ( 6 , 9 , 15 17 , 21 , 39 , 42 , 43 ). In this study, we found statistically significant differences for the magnitude of WSS between HV and patients with BAV with AAo dilated and all patients together.…”
Section: Discussionmentioning
confidence: 99%